Ionic/hydrogen-bonding dual-network orchestration in sulfonated-OPBI via phytic acid-PEI nanoarchitectonics of PAFs for efficient proton transfer highways - Fei Chen; Xinyi Zong; Xianfeng Guan; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Nanofiber ionic bridge framed quasi-solid polymer electrolyte with nanocellulose and PAF for improved low-temperature lithium battery - Jiayi Luo; Shenyuan Li; Yangyang Yu; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Molecular insights into Yb(III) speciation in sulfate-bearing hydrothermal fluids from X-ray absorption spectra informed by ab initio molecular dynamics - Xiaodong Zhao; Duo Song; Sebastian T. Mergelsberg; Micah P. Prange; Daria Boglaienko; Zihua Zhu; Zheming Wang; Carolyn I. Pearce; Chengjun Sun; Kevin M. Rosso; Xiaofeng Guo; Xin Zhang (Geochimica et Cosmochimica Acta, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

4D printed kirigami metamaterial with reconfigurability for dual-mode displacement-pressure sensing - Song Liu; Zhaoxuan Niu; Wei Zhao; Chengjun Zeng; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Elevational shift in seed plant distributions in China's mountains over the last 70 years - Kuiling Zu; Jonathan Lenoir; Jingyun Fang; Zhiyao Tang; Zehao Shen; Chengjun Ji; Chengyang Zheng; Ao Luo; Wenqi Song; Niklaus E. Zimmermann; Loïc Pellissier; Zhiheng Wang (Global Ecology and Biogeography, 2023)
Aim Significant changes in species elevational ranges in mountains have been repeatedly documented, yet the direction, magnitude and drivers of these shifts remain controversial. Presently, there is still lacking evidence about the general nature of species elevational range shifts in eastern Eurasia in response to anthropogenic climate change. By using historical specimen records and recent field observations for 735 seed plant species across 29 China's mountains, we assessed changes in species' elevational centroids and their drivers. Location China. Time Period 1950–2018. Major Taxa Studied Seed plant species. Methods The elevation records of all sampled occurrences in each mountain during the two time periods were estimated, and the null models were developed to test the sampling bias. Ecological niche models (ENMs) were used to evaluate the relative importance of climate factors in constraining each species distribution. Generalized linear models (GLMs) to test the relationships between the centroid elevational range shifts of species and different divers. Results We found that 54% of the species shifting upward and 46% downhill. However, species' elevational shifts significantly differed among species and mountains. Herbaceous and lowland species moved upward faster than woody and high‐elevation species. Species in temperate mountains and in mountains with taller elevational gradients moved upward, while species in subtropical mountains and in mountains with shorter elevational gradients moved downward. Precipitation changes experienced by species, species' climatic adaptations, several species' functional traits and mountain size all contributed to explain the magnitude of species' centroid elevational range shifts. Main Conclusions Our results highlight complex biodiversity redistribution of seed plants across Chinese mountains, not necessarily conforming to the trend of species upward shifts in elevation. Changes in precipitation regimes may blur the simplistic assumption of isotherm tracking. This study fills an important geographic shortfall for our understanding of biodiversity redistribution under anthropogenic climate change.

Multiple-functionalized biochar affects rice yield and quality via regulating arsenic and lead redistribution and bacterial community structure in soils under different hydrological conditions - Xing Yang; Zhinan Dai; Chengjun Ge; Huamei Yu; Nanthi Bolan; Daniel C.W. Tsang; Hocheol Song; Deyi Hou; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Unraveling the joint toxicity of transition-metal dichalcogenides and per- and polyfluoroalkyl substances in aqueous mediums by experimentation, machine learning and molecular dynamics - Guohong Liu; Xiliang Yan; Chengjun Li; Song Hu; Jiachen Yan; Bing Yan (Journal of Hazardous Materials, 2023)

Iron-modified phosphorus- and silicon-based biochars exhibited various influences on arsenic, cadmium, and lead accumulation in rice and enzyme activities in a paddy soil - Xing Yang; Ergang Wen; Chengjun Ge; Ali El-Naggar; Huamei Yu; Shengsen Wang; Eilhann E. Kwon; Hocheol Song; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

The decomposition rates of leaf litter and fine root and their temperature sensitivities are influenced differently by biotic factors - Shanshan Song; Xiaokang Hu; Jiangling Zhu; Tianli Zheng; Fan Zhang; Chengjun Ji; Jianxiao Zhu (Plant and Soil, 2021)

Migration of phthalates from plastic packages to convenience foods and its cumulative health risk assessments - Jinling Yang; Weizhong Song; Xiaojie Wang; Yongxin Li; Jiannan Sun; Weilei Gong; Chengjun Sun (Food Additives & Contaminants Part B-Surveillance, 2019)

Complete genome sequence of Lactococcus lactis subsp. lactis SLPE1-3, a novel lactic acid bacterium causing postharvest decay of the mushroom Pleurotus eryngii - Yancun Zhao; Runjie Zhu; Ying Wang; Zhiwei Song; Chengjun Shan; Jingping Qiu; Fengquan Liu (Journal of Plant Pathology, 2018)

Effects of plant coverage on shrub fertile islands in the Upper Minjiang River Valley - Laiye Qu; Zhongbin Wang; Yuanyuan Huang; Yuxin Zhang; Chengjun Song; Keming Ma (Science China Life Sciences, 2018)

Retraction Note to: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2017)

Validation of the quantitative trait locus underlying soybean plant height using residual heterozygous lines and near-isogenic lines across multi-environments - Long Yan; Yuanyuan Zhang; Qijian Song; Perry B. Cregan; Chunyan Yang; Yongqiang Charles An; Chengjun Wu; Qiang Chen; Bingqiang Liu; Rui Di; Mengchen Zhang (Euphytica, 2017)

RETRACTED ARTICLE: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2016)

The study of the adductor muscle-shell interface structure in three Mollusc species - Yaoyao Zhu; Chengjun Sun; Yingfei Song; Fenghua Jiang; Xiaofei Yin; Min Tang; Haibing Ding (Acta Oceanologica Sinica, 2016)

Methodology for antibody preparation and detection of southern rice black-streaked dwarf virus - Zhuo Chen; Chengjun Yin; Jiaju Liu; Mengjiao Zeng; Zhenchao Wang; Dandan Yu; Liang Bi; Linhong Jin; Song Yang; Baoan Song (Archives of Virology, 2012)

Comparison of sociability, parental care and central estrogen receptor alpha expression between two populations of mandarin voles (Microtus mandarinus) - Ruiyong Wu; Aifang Yuan; Qinwei Yuan; Rui Guo; Fadao Tai; Zhenzhen Song; Chengjun Yu (Journal of Comparative Physiology A, 2011)